Targeting Macrophages: Friends or Foes in Disease? - Ardura, Juan A.; Rackov, Gorjana; Izquierdo, Elena; Alonso, Veronica; Gortazar, Arancha R.; Escribese, Maria M. (Frontiers in Pharmacology, 2019)
Macrophages occupy a prominent position during immune responses. They are considered the final effectors of any given immune response, since they can be activated by a wide range of surface ligands and cytokines to acquire a continuum of functional states. Macrophages are involved in tissue homeostasis and in the promotion or resolution of inflammatory responses, causing tissue damage or helping in tissue repair. Knowledge in macrophage polarization has significantly increased in the last decade. Biomarkers, functions and metabolic states associated with macrophage polarization status have been defined both in murine and human models. Moreover, a large body of evidence demonstrated that macrophage status is a dynamic process that can be modified. Macrophages orchestrate virtually all major diseases — sepsis, infection, chronic inflammatory diseases (rheumatoid arthritis), neurodegenerative disease and cancer — and thus they represent attractive therapeutic targets. In fact, the possibility to “reprogram” macrophage status is considered as a promising strategy for designing novel therapies. Here, we will review the role of different tissue macrophage populations in the instauration and progression of inflammatory and non-inflammatory pathologies, as exemplified by rheumatoid arthritis, osteoporosis, glioblastoma, and tumor metastasis. We will analyze: 1) the potential as therapeutic targets of recently described macrophage populations, such as osteomacs, reported to play an important role in bone formation and homeostasis or metastasis-associated macrophage (MAMs), key players in the generation of premetastatic niche; 2) the current and potential future approaches to target monocytes/macrophages and their inflammation-causing products in rheumatoid arthritis and 3) the development of novel intervention strategies using oncolytic viruses, immunomodulatory agents and checkpoint inhibitors aiming to boost M1-associated anti-tumor immunity. In this review we will focus on the potential of macrophages as therapeutic targets and discuss their involvement in state-of-the-art strategies to modulate prevalent pathologies of ageing societies.